Impact of cardiac amyloidosis on outcomes of patients hospitalized with heart failure in Germany. (14th October 2021) - Goebel, S; Hobohm, L; Desuki, A; Gori, T; Muenzel, T; Rapezzi, C; Wenzel, P; Keller, K
Abstract: Background: Amyloidosis is a multi-systemic disease resulting from deposition of misfolded proteins as insoluble fibrils in the interstitium of affected organs including the heart, subsequently leading to organ failure. Cardiac involvement is predominantly observed in light chain (AL) amyloidosis and wild-type transthyretin (ATTRwt) amyloidosis. Purpose: We aimed to investigate prevalence and prognostic implications of cardiac amyloidosis of any etiology on outcomes of hospitalized patients with heart failure (HF) in Germany. Methods: We analyzed data of the German nationwide inpatient sample (2005–2018) of patients hospitalized for HF (including myocarditis with HF and heart transplantation with HF). HF patients with amyloidosis (defined as cardiac amyloidosis [CA]) were compared with those HF patients without amyloidosis and impact of CA on outcomes was assessed (source: Research Data Center (RDC) of the Federal Statistical Office and the Statistical Offices of the federal states, DRG Statistics 2005–2018, and own calculations). Results: During this fourteen-year observational period 5, 478, 835 hospitalizations of HF patients were analyzed. Amyloidosis was coded in 5, 407 hospitalizations of HF patients (0.1%). Prevalence of CA was 1.87 hospitalizations per 100, 000 German population. CA patients were younger (75.0 [IQR 67.0/80.0] vs. 79.0 [72.0–85.0] years, p<0.001), predominantly male (68.9%) and had a higher prevalence of cancer (14.8% vs. 3.6%, P<0.001) compared with HF without amyloidosis. Although patients without amyloidosis had a pronounced cardiovascular risk profile -especially arterial hypertension (45.4% vs. 35.6%; p<0.001) and diabetes mellitus (38.9% vs. 18.5%; p<0.001)- and a higher prevalence of concomitant coronary artery disease (40.5% vs. 34.5%; p<0.001) and chronic obstructive pulmonary disease (17.1% vs. 9.4%; p<0.001), adverse in-hospital events including necessity of transfusions of blood constituents (7.1% vs. 5.4%, p<0.001) and cardio-pulmonary resuscitation (CPR, 2.7% vs. 1.4%; p<0.001) were more frequent in CA. CA was independently associated with acute kidney failure (OR 1.40 [95% CI 1.28–1.52], p<0.001), CPR (OR 1.58 [95% CI 1.34–1.86], p<0.001), intracerebral bleeding (OR 3.13 [95% CI 1.68–5.83], p<0.001) and in-hospital mortality in the 6th and 8th decade of life (6thdecade: OR 1.40 [95% CI 1.01–1.94], p=0.042; 8thdecade: OR 1.18 [95% CI 1.03–1.35], p=0.02). Conclusions: CA was identified as an independent risk factor for complications and in-hospital mortality in HF patients. Physicians should be aware of this issue concerning treatments and monitoring of CA-patients. Funding Acknowledgement: Type of funding sources: None.